2022
DOI: 10.4155/fmc-2022-0252
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ATM Inhibitors As Potential Therapeutic Agents

Abstract: ATM, a member of the phosphatidylinositol-3-kinase-like protein family, plays a central role in responding to DNA double-strand breaks and other lesions to protect the genome against DNA damage. Loss of ATM’s kinase function has been shown to increase the sensitivity of most cells to ionizing radiation. Therefore, ATM is thought to be a promising target for chemotherapy as a radiotherapy sensitizer. The mechanism of ATM in cancer treatment and the development of its inhibitors have become research hotspots. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Moreover, numerous proteins associated with DDR within the ATM-P53 pathway, as well as its downstream pathways, were significantly modulated, as depicted in Figure S1. Given the pivotal role of ATM in cancer initiation and progressions, 42 its identification as a potential target prompted us to proceed with further validation studies.…”
Section: Proteomic Profiling Of 9b Against Cancer Cellsmentioning
confidence: 99%
“…Moreover, numerous proteins associated with DDR within the ATM-P53 pathway, as well as its downstream pathways, were significantly modulated, as depicted in Figure S1. Given the pivotal role of ATM in cancer initiation and progressions, 42 its identification as a potential target prompted us to proceed with further validation studies.…”
Section: Proteomic Profiling Of 9b Against Cancer Cellsmentioning
confidence: 99%
“…For instance, ATM inhibitors are being tested in clinical trials. While pre‐clinical studies show a synergy between ATM inhibitors and DNA damaging agents, [ 158,159 ] we and others have shown that ATM has effects outside of the DDR. [ 146 ] Indeed, our recent study found that inhibition of ATM increases nutrient uptake and promotes survival of ovarian cancer.…”
Section: Future Perspectivesmentioning
confidence: 99%